Ecological urbanism : the nature of the city - Hagan, Susannah (Abingdon, Oxon ; New York, NY : Routledge, 2015)
"Ecological Urbanism: The Nature of the City asks the questions that are important inside and outside the built environment professions: what are climate change, urbanisation and ecology doing to the theory and practice of urban design? How does Ecological Urbanism figure in this change? What is Ecological Urbanism? In answer, this book is neither definitive - impossible when a subject is still in motion - nor encyclopaedic - equally impossible when so much has been written on almost every aspect of these essays. Instead, it seeks to rebalance the ecological narrative and its embryonic modes of practice with the narratives of urbanism and its older, deeply embedded modes of practice. It examines the implications for cities and the designers of cities now we are required to again address their metabolic as well as social and formal dimensions, and it explores the extent to which environmental engineering and natural systems design can and should become drivers for the remaking of cities in the 21st century. Above all, it argues that sooner rather than later, urbanism needs to become environmentally literate, and environmental design needs to become culturally literate"--
Includes bibliographical references and index.
Keywords: Urban ecology (Sociology); POLITICAL SCIENCE / Public Policy / City Planning & Urban Development